Inhibition of left anterior intraparietal sulcus shows that mutual adjustment marks dyadic joint-actions in humans. Issue 5 (5th April 2018) - Era, Vanessa; Candidi, Matteo; Gandolfo, Marco; Sacheli, Lucia Maria; Aglioti, Salvatore Maria
Abstract: Creating real-life dynamic contexts to study interactive behaviors is a fundamental challenge for the social neuroscience of interpersonal relations. Real synchronic interpersonal motor interactions involve online, inter-individual mutual adaptation (the ability to adapt one's movements to those of another in order to achieve a shared goal). In order to study the contribution of the left anterior Intra Parietal Sulcus (aIPS) (i.e. a region supporting motor functions) to mutual adaptation, here, we combined a behavioral grasping task where pairs of participants synchronized their actions when performing mutually adaptive imitative and complementary movements, with the inhibition of activity of aIPS via non-invasive brain stimulation. This approach allowed us to investigate whether aIPS supports online complementary and imitative interactions. Behavioral results showed that inhibition of aIPS selectively impairs pair performance during complementary compared to imitative interactions. Notably, this effect depended on pairs' mutual adaptation skills and was higher for pairs composed of participants who were less capable of adapting to each other. Thus, we provide the first causative evidence for a role of the left aIPS in supporting mutually adaptive interactions and show that the inhibition of the neural resources of one individual of a pair is compensated at the dyadic level.